COMPARATIVE STUDY OF OXCARBAZEPINE VERSUS BACLOFEN FOR THE PREVENTION OF RELAPSE IN ALCOHOL DEPENDENCE SYNDROME PATIENTS - MUGHILAN K; AMIRTHA RT; SRI SNEKHA B; DEVA PRATHIMAA VS; NATRAJAN SHANMUGASUNDHARAM; KARTHIK THIYAGARAJAN; RAGESH GURUMOORTHI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Alcohol Dependence Syndrome (ADS) is a chronic disorder characterized by both physical and psychological dependence on alcohol, leading to significant health complications. Despite advances in pharmacotherapy and psychological interventions, relapse remains a major challenge. Baclofen and oxcarbazepine have shown potential in reducing relapse rates. This study evaluates the effectiveness of oxcarbazepine versus baclofen in preventing relapse in ADS patients. Methods: A six-month study was conducted at Sri Ramachandra Institute of Higher Education and Research, involving 59 male patients undergoing treatment for alcohol withdrawal and ADS. Participants were divided into three groups: Group A (Baclofen), Group B (Oxcarbazepine), and Group C (Combination of Baclofen and Oxcarbazepine). Relapse rates and craving levels were assessed using the Alcohol Relapse Risk Scale (ARRS), Penn Alcohol Craving Scale (PACS), and Warning of Relapse (AWARE) scale. Results: Patients in the combination therapy group (Group C) exhibited a significantly lower relapse rate compared to Groups A and B. Statistically significant improvements in attitude toward treatment were observed across all groups at the first follow-up (45 days), with the most pronounced improvement in Group C. The ARRS, PACS, and AWARE scales confirmed the superior effectiveness of combination therapy in reducing both relapse and cravings. Conclusion: Alcohol dependence is a treatable disorder, and pharmacotherapy plays a crucial role in managing withdrawal symptoms and preventing relapse. The combination of oxcarbazepine and baclofen appears to be more effective than monotherapy in reducing relapse rates and cravings in ADS patients.